One pavilion eight palaces: The construction of German identity in Barcelona 1929 - Martínez de Guereñu, Laura (CSIC Consejo Superior de Investigaciones Cientificas, 2019)
This article resolves a historiographical omission,disclosing the forgotten context of the German Pavilion at the 1929 Barcelona International Exposition. Much scholarship has been produced around the myth of a Pavilion that,in spite of its ephemeral existence of eight months,became one of the most important works of the 20th century. However,the formal relationship between the architectural elements of the Pavilion and the design of the 16,000 m2 of German industrial sections distributed in eight Noucentista Palaces had not been explored until now. This article reveals the construction of a consistent sequence linking the Pavilion and the interior of these Palaces,which allowed Mies and Lilly Reich to architecturally express the distinctive identity of Germany through the recovered strength of its industrial fabric. © 2019 CSIC.
[UN PABELLÓNOCHO PALACIOS: LA CONSTRUCCIÓN DE LA IDENTIDAD ALEMANA EN BARCELONA 1929]
Keywords: Design; Identity; Industry; International exhibitions; Lilly Reich; Ludwig Mies van der Rohe; Modernism; Noucentisme; Pavilion; Sequence; 55 Historia::5506 Historia por especialidades::5506.01 Historia de la arquitectura; ODS 4 - Educación de calidad; ODS 3 - Salud y bienestar